Evidence of 68Ga-DOTA-NT-20.3 Uptake in Pancreatic Adenocarcinoma AsPC-1 Cell Line – in vitro Study - Marenco, Manuela; Lodola, Lorenzo; Persico, Marco G.; Frangipane, Vanessa; Facoetti, Angelica; Aprile, Carlo; Hodolič, Marina (Current Pharmaceutical Biotechnology, 2018)
Background: Neurotensin receptors are overexpressed in several cancer types including pancreatic ductal adenocarcinoma. Three NTR subtypes have been cloned: NTR-1, NTR-2 and NTR-3. The most expressed NTR-1 is not present in normal pancreatic tissue and has a low expression in chronic pancreatitis. Objective: Objective of this study was to test in vitro affinity of the new 68Ga labelled neurotensin analogue DOTA-NT-20.3 (fragment 6-13, Ac-Lys(DOTA)-Pro-Arg(N-CH3)-Arg-Pro-Tyr-Tle-Leu) on the human pancreatic ductal adenocarcinoma cell line AsPC-1. Method: For the preparation of 68Ga-DOTA-NT-20.3, 68GaCl3 solution (eluted from 68Ge/68Ga generator) and 50 μg of precursor (Iason, Graz, Austria) water dissolved were used in an automatic synthesis module. The labeled compound was added to cell culture flask and incubated at 37°C. At various time points after tracer addition up to 80min, cells were recovered, rinsed and counted for radioactivity. Results were expressed as percent binding normalized to 200000 cells and affinity parameters were calculated. Results: Labeling yield was ≥98 %. The molar ratio between labelled and total peptide was about 1/400. AsPC-1 cell line showed rapid uptake of the tracer including surface and internalized binding, tending to a plateau phase 80 min after tracer addition (11%/200.000 cells). The Kd (7.335 pmol) and Bmax (90.52 kBq) value indicated high tracer affinity for AsPC-1cell line especially if compared with the literature data regarding other malignancies (e.g. colonic cancer cell line). Binding sites were 1.09x106 sites per cell. Conclusion: New tracer 68Ga-DOTA-NT-20.3 can be a suitable candidate for the clinical use in patients with pancreatic ductal adenocarcinoma.
Keywords: NTR-1